Assessing the effects of gamification in the classroom: A longitudinal study on intrinsic motivation, social comparison, satisfaction, effort, and academic performance - Hanus, Michael D.; Fox, Jesse (Computers and education, 2015)
Gamification, the application of game elements to non-game settings, continues to grow in popularity as a method to increase student engagement in the classroom. We tested students across two courses, measuring their motivation, social comparison, effort, satisfaction, learner empowerment, and academic performance at four points during a 16-week semester. One course received a gamified curriculum, featuring a leaderboard and badges, whereas the other course received the same curriculum without the gamified elements. Our results found that students in the gamified course showed less motivation, satisfaction, and empowerment over time than those in the non-gamified class. The effect of course type on students' final exam scores was mediated by students' levels of intrinsic motivation, with students in the gamified course showing less motivation and lower final exam scores than the non-gamified class. This suggests that some care should be taken when applying certain gamification mechanics to educational settings. •Longitudinal study on effects of gamification in the classroom.•71 students surveyed at four time points in gamified or non-gamified course.•Over time, gamified students were less motivated, empowered, and satisfied.•Gamified course negatively affected final exam grades through intrinsic motivation.•Gamified systems strongly featuring rewards may have negative effects.